A Modified Single-Phase Single-Stage Boost Inverter - Hadi Khoramdel; Farzad Sedaghati; Hossein Shayeghi; Hadi Dolati (مجله مدل سازی در مهندسی)
This paper presents a modified single stage single phase inverter with four switches. The proposed inverter has important features such as continuous input current, voltage buck and boost with single stage conversion, short circuit safety and operation in various duty cycles same as qZSI and qSBI converters. In the rest of the paper, the suggested inverter operation mode and its switching method are described first and then, the steady state analysis is presented. To validate the merits of the proposed inverter, a comparison of the converter with similar topologies is provided. To verify the proper operation of the converter and also, to prove the presented theoretical calculations, a prototype of the introduced topology has been implemented in the laboratory. Test measurement results of the suggested inverter in 150 W with 10kHz frequency is derived. The obtained results and waveforms from test measurement present proposed inverter operation, steady state analysis and performance..